ASESMEN DIAGNOSTIK PENDIDIKAN AGAMA ISLAM DALAM KURIKULUM MERDEKA: ANALISIS EFEKTIVITAS, INSTRUMEN, DAN IMPLIKASI PEMBELAJARAN DIFERENSIATIF - Yasin, Ahmad; Lubna; Mukhlis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of diagnostic assessment in mapping students’ cognitive and spiritual readiness in Islamic Religious Education (PAI) within the implementation of the Merdeka Curriculum. This research employed a qualitative descriptive approach using a Systematic Literature Review (SLR) design strengthened by a hypothetical conceptual framework of integrative diagnostic assessment. The findings indicate that diagnostic assessment effectively identifies students’ prior knowledge and misconceptions through case-based tests and two-tier instruments. However, measuring spiritual dimensions requires authentic assessment approaches such as observation, reflective journals, and performance-based evaluation. Diagnostic assessment provides empirical foundations for differentiated instruction, particularly in planning remedial, enrichment, and character-based interventions. Despite its pedagogical significance, implementation challenges remain, including teachers’ assessment literacy, time constraints, and difficulties in interpreting non-cognitive data. The study recommends the development of an integrative cognitive–spiritual diagnostic assessment model to strengthen Islamic Religious Education practices in primary education.